2008
DOI: 10.1080/00365520701885507
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 promoter polymorphisms influence susceptibility to ulcerative colitis in a gender-specific manner

Abstract: A gender effect is observed, with women of AG/AA IL10 genotypes and AC/AT haplotypes having a higher risk of developing UC at a younger age. This finding could be related to the previously documented lower IL10 production associated with the -1082A allele and to the IL10 down-regulating effect of estrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…In subsequent studies, IL10 promoter polymorphisms were sporadically associated with IBD. For example, G-1082A SNPs was associated with UC and/or CD in Spanish, Australian, New Zealand, Italian, and Mexican studies (Fernandez et al 2005;Fowler et al 2005;Castro-Santos et al 2006;Hong et al 2008;Tedde et al 2008;Garza-Gonzalez et al 2010;Wang et al 2011), but the findings were not consistent, showing associations for both G and A allele (or genotypes containing those alleles). The polymorphism C-592A was also associated with CD in Canadian pediatric patients (Amre et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…In subsequent studies, IL10 promoter polymorphisms were sporadically associated with IBD. For example, G-1082A SNPs was associated with UC and/or CD in Spanish, Australian, New Zealand, Italian, and Mexican studies (Fernandez et al 2005;Fowler et al 2005;Castro-Santos et al 2006;Hong et al 2008;Tedde et al 2008;Garza-Gonzalez et al 2010;Wang et al 2011), but the findings were not consistent, showing associations for both G and A allele (or genotypes containing those alleles). The polymorphism C-592A was also associated with CD in Canadian pediatric patients (Amre et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, IL-10-1082 G/A polymorphism has been reported to influence susceptibility to UC [38,86,126]. A gender effect has been reported, with women of AG/AA genotypes of IL-10-1082 G/A, having a higher risk of developing UC at a younger age and is related to the lower IL-10 production associated with the -1082A allele and to the IL10 downregulating effect of estrogens [86].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the IL-10 promoter polymorphisms and IBD susceptibility have also been inconsistent [71,[83][84][85][86][87][88][89]. Some studies have found an associations between IL-10 polymorphism and IBD [71,86,87,90], whereas other studies were unable to find any association between IBD and the IL-10 promoter polymorphisms [83,84,88,91].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, a total of 7 case-control studies met the preset inclusion criteria, in which 1890 cases and 2929 controls were included for the pooled analysis [15][16][17][18][19][20][21] . The characteristics of the studies are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%